Analysis of Micro Business Management Strategies in Efforts to Maintain Business Sustainability - et. al., Yoga Tantular Rachman, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to analyze the effective and efficient long-term management of micro-businesses in an effort to increase operating profits and the sustainability of these businesses. The application of management accounting, such as determining the cost of goods sold, selling price, then financial accounting in preparing financial reports and marketing strategies, is the focus of this research. The method used in this research is a descriptive method based on sources from the literature (journals, articles, books, etc.).The results of this study will provide a strong picture of the implementation of strategies in micro-business management in an effort to increase income, profit and business sustainability. An accurate determination of the cost of goods manufactured will determine the accuracy in determining the product's selling price and determine the right marketing strategy. Adequate financial reporting will provide information for the business itself in determining future business development.